The use of a non-invasive extendable prosthesis at the time of revision arthroplasty. (March 2018) - Gilg, M. M.; Gaston, C. L.; Jeys, L.; Abudu, A.; Tillman, R. M.; Stevenson, J. D.; Grimer, R. J.; Parry, M. C.
Abstract : Aims: The use of a noninvasive growing endoprosthesis in the management of primary bone tumours in children is well established. However, the efficacy of such a prosthesis in those requiring a revision procedure has yet to be established. The aim of this series was to present our results using extendable prostheses for the revision of previous endoprostheses. Patients and Methods: All patients who had a noninvasive growing endoprosthesis inserted at the time of a revision procedure were identified from our database. A total of 21 patients (seven female patients, 14 male) with a mean age of 20.4 years (10 to 41) at the time of revision were included. The indications for revision were mechanical failure, trauma or infection with a residual leg-length discrepancy. The mean follow-up was 70 months (17 to 128). The mean shortening prior to revision was 44 mm (10 to 100). Lengthening was performed in all but one patient with a mean lengthening of 51 mm (5 to 140). Results: The mean residual leg length discrepancy at final follow-up of 15 mm (1 to 35). Two patients developed a deep periprosthetic infection, of whom one required amputation to eradicate the infection; the other required two-stage revision. Implant survival according to Henderson criteria was 86% at two years and 72% at five years. When considering revision for any cause (including revision of the growing prosthesis to a non-growing prosthesis), revision-free implant survival was 75% at two years, but reduced to 55% at five years. Conclusion: Our experience indicates that revision surgery using a noninvasive growing endoprosthesis is a successful option for improving leg length discrepancy and should be considered in patients with significant leg-length discrepancy requiring a revision procedure. Cite this article: Bone Joint J 2018;100-B:370–7.